Equatorial Guinea Education Sector Diagnostic - Bassett, Lucy (World Bank, Washington, DC, 2017)
The Government of Equatorial Guinea (GoEG) requested financial, analytical, and technical support from the World Bank during the country’s protracted economic recession. Given the prioritization of education in the country’s national development plan, the World Bank agreed to undertake an education sector diagnostic study to: (a) help the World Bank better understand the education sector, including the main challenges and policy priorities of the government; (b) facilitate dialogue between the World Bank and GoEG in the education sector and suggest options to move forward in the current economic downturn; (c) provide supporting background for a parallel activity that is focusing on public expenditures in the social sector (public expenditure review (PER)); (d) support the activities that are planned as part of the national development plan’s programa mayor educación para todos; and (e) provide education sector stakeholders with an updated summary of the sector including a review of recent indicator trends and program activities. This diagnostic focuses primarily on primary and secondary education, while also providing some information on technical and vocational education and training (TVET) and higher education, especially where relevant to the other subsectors. It is also intended to update an earlier World Bank-supported education sector diagnostic. The diagnostic is divided into three main parts. Part A focuses on country context, background on the education sector, and recent trends in education (for example, enrollment, and repetition). Part B moves into the education sector diagnostic by topic, focusing on the main challenges in areas such as education finance, quality, and learning outcomes. Part C introduces possible policy actions, framed with the current crisis context, that address some of the main issues identified in Part B.